Implementasi Program Kampus Mengajar untuk Meningkatkan Karakter Gemar Membaca melalui Kegiatan Literasi di SD Negeri Pucangan 05 Kabupaten Sukoharjo - Dhani, Nabila Risma; Wibowo, Yunus Aris (Warta LPM, 2025)
SD Negeri Pucangan 05 is one of the schools with a low literacy rate, as evidenced by 28 % students who still demonstrate low reading skills. Consequently, this teaching campus program focuses on fostering a reading culture among students through literacy activities. Program implementation is carried out using methods starting from the activity planning, implementation phase, and follow-up or evaluation activities. The target group for this activity included all 75 students at SD Negeri Pucangan 05. Based on the program, results showed that students' literacy skills improved. The improvement in literacy was achieved through various activities such as book reviews, film literacy, dream trees, study clinics, basic literacy and numeracy (calistung), and library revitalization. The success of this program was supported by the innovation introduced, allowing students to learn through diverse and engaging media, thus enabling effective literacy enhancement efforts. Additionally, the active involvement of university students as teacher partners in this activity demonstrated a significant increase in students' reading enthusiasm. This activity has great potential to be implemented by the school because the simple and innovative method has been transformed by the teachers of Pucangan 05 Elementary School. In addition, this activity has a good impact on students and schools, so it is very appropriate to implement it routinely.